Adrenal and Gonadal Activity, Androgen Concentrations, and Adult Height Outcomes in Boys With Silver-Russell Syndrome - Kvernebo Sunnergren, Kjersti; Ankarberg-Lindgren, Carina; Dahlgren, Jovanna (Frontiers in Endocrinology, 2019)
Background: We have previously shown that adult height (AH) in males with Silver-Russell syndrome (SRS) correlated negatively with prepubertal estradiol concentrations. We aimed to identify the source of estradiol by analyzing androgen secretion profiles and measuring anti-Müllerian hormone (AMH) and inhibin B concentrations during childhood and puberty in this group of patients. Methods: In a retrospective longitudinal single-center study, 13 males with SRS were classified as nonresponders (NRs=8) or responders (Rs=5), depending on the AH outcome. From 6 years of age, androgens were determined by mass spectrometry, and AMH, inhibin B and sex hormone-binding globulin concentrations were analyzed by immunoassays. Results: AH outcome correlated negatively with dehydroepiandrosterone-sulfate (DHEAS) at 8 (r=-0.72), 10 (r=-0.79) and 12 years (r=-0.72); testosterone at 10 (r=-0.94), 12 (r=-0.70) and 14 years (r=-0.64); dihydrotestosterone (DHT) at 10 (r=-0.62) and 12 years; (r=-0.57) and AMH at 12 years (r=0.62) of age. Compared with Rs, NRs had higher median concentrations of DHEAS (mol/L) at 10 years (2.9 versus 1.0); androstenedione (nmol/L) at 10 (1.1 versus 0.6) and 12 years (1.7 versus 0.8); testosterone (nmol/L) at 10 (0.3 versus 0.1), 12 (7.8 versus 0.2) and 14 years (15.6 versus 10.4); and DHT (pmol/L) at 10 (122 versus 28) and 12 years (652 versus 59) of age. AMH (ng/mL) was lower in NRs than in Rs at 12 years of age (11 versus 50). No significant differences were observed in the inhibin B concentrations at any age. Conclusions: The elevated androgen concentrations before and during puberty, originated from both adrenal and gonadal secretion and correlated negatively with AH outcomes in males with SRS.